The Energy Trilemma and the Smart Grid: Implications Beyond the United States. Issue 1 (5th January 2017) - Oliver, Jeannie; Sovacool, Benjamin
Abstract: This article argues that smart grid technologies enable policy‐makers and communities to successfully manage enduring energy policy concerns. It defines what 'smart' energy technologies, grids and policies mean, and then evaluates how the smart grid can enable policy‐makers to respond to an emerging energy 'trilemma'. Drawing on case studies from the United States, the article suggests that the automated communications enabled by smart grid technologies significantly benefit each dimension of the energy trilemma: economic, social and environmental. However, successful smart grid implementation requires smart communication beyond technology. Failure to engage with customers through targeted communication, or to adequately address customers' privacy concerns, risks alienating customers, threatening the value of the smart grid investment. This article concludes that, with smart communication, both technical and human, the smart grid is an important step towards a sustainable energy future for stakeholders well beyond the United States.